Industria cementera en Colombia y su impacto internacional (2020)
The document presented below seeks to demonstrate the main economic models of internationalization used by Cementos Argos to consolidate abroad specifically in the United States, the Caribbean and Central America in a successful manner with positive consequences for the organization and for Colombia, all this is based on knowing its history and evolution over the years, also identifying the most relevant political variables and the good practices accepted by the company. Finally, an evaluation is made of the most relevant and high-impact international models used by Argos that can be applied to companies in the cement sector in the country.